Some Aspects of Intercropping Ratian (Calamus Manan Miq.) With Rubber (Hevea Brasiliensis Willd.) in Malaysia - Myint, Win (2000)
Intercropping rattan with mature rubber trees is a new agroforestry system. This study was carried out in a 10-year old rattan plantation that had been intercropped with rubber when the rubber trees were 6-years old. This study focused on the aspects of soil conservation, growth of rattan and rubber, and economic viability. The study comprises of four experiments and economic analysis. The first experiment assessed the effects of rattan planting on some selected soil properties. The results showed no significant adverse effects but improvement in bulk density, moisture content, soil acidity (PH) and cation exchange capacity (CEC). In addition, there was a significant increase in total phosphorous (P), magnesium (Mg) and sodium (Na). The second experiment on foliar analysis revealed that there was no significant negative effect on foliar nutrients of rubber due to intercropping. Besides, the nutrient concentrations in rattan leaves were not significantly different from than that of rubber. The third experiment also demonstrated no significant effect on growth of rubber trees in terms of diameter breast height (dbh) and height of main trunk due to intercropping.